2010
DOI: 10.1158/0008-5472.can-10-1546
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of MDM2 by the Interaction between Berberine and DAXX Leads to Potent Apoptosis in MDM2-Overexpressing Cancer Cells

Abstract: Berberine, a natural product derived from a plant used in Chinese herbal medicine, is reported to exhibit anticancer effects; however, its mechanism of action is not clearly defined. Herein, we demonstrate that berberine induces apoptosis in acute lymphoblastic leukemia (ALL) cells by downregulating the MDM2 oncoprotein. The proapoptotic effects of berberine were closely associated with both the MDM2 expression levels and p53 status of a set of ALL cell lines. The most potent apoptosis was induced by berberine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 37 publications
3
113
0
Order By: Relevance
“…Consistent with its long-standing liver protective effects, berberine has been shown to exhibit anticachectic effect in a colon cancer-bearing mouse model (25), and to induce the growth related gene rcl, in a rat hepatoma cell line (27). Recent reports indicate that p53 and p38 MAPK pathways are involved in berberine anticancer activity (28,29). Although these studies have provided some understanding about the functions of berberine, the exact molecular mechanisms are unknown.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with its long-standing liver protective effects, berberine has been shown to exhibit anticachectic effect in a colon cancer-bearing mouse model (25), and to induce the growth related gene rcl, in a rat hepatoma cell line (27). Recent reports indicate that p53 and p38 MAPK pathways are involved in berberine anticancer activity (28,29). Although these studies have provided some understanding about the functions of berberine, the exact molecular mechanisms are unknown.…”
Section: Discussionmentioning
confidence: 91%
“…Berberine can induce apoptosis in a variety of cancer cells (12,13,(18)(19)(20). We, therefore, determined whether berberine could also induce apoptosis of glioblastoma cells.…”
Section: Berberine Induces Cellular Senescence Of Glioblastoma Cellsmentioning
confidence: 99%
“…Zhang et al also reported that berberine triggers apoptosis in acute lymphoblastic leukemia cells through down-regulating the MDM2 (21). Because the role of p53 has been emerging in cell cycle and apoptosis of cancer cells, we also investigated the effect of berberine on p53 mRNA and protein expression in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 90%
“…The function of p53 is known in a variety of cell types including the arrest of cell cycle, cellular senescence, and apoptosis (19,21). p21 and Polo-like kinase 1 are important targets of p53 for G1/S and G2-M cell cycle checkpoint activation, respectively (15).…”
Section: Discussionmentioning
confidence: 99%